1994
DOI: 10.1007/bf00176576
|View full text |Cite
|
Sign up to set email alerts
|

Drug interactions with radiopharmaceuticals

Abstract: Considerable information on documented drug and radiopharmaceutical interactions has been assembled in a tabular form, classified by the type of nuclear medicine study. The aim is to provide a rapid reference for nuclear medicine staff to look for such interactions. The initiation of drug chart monitoring or drug history taking of nuclear medicine patients and the reporting of such events are encouraged.Reduced tumour uptake Reduced tumour uptake Reduced tumour uptake Reduced tumour uptake Increased tumour ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
0
28
0
2
Order By: Relevance
“…The in vitro effect of the Uncaria tomentosa extract on radiolabeling of blood constituents may be due to four possible mechanisms: (i) chelation of stannous and/or pertechnetate ions; (ii) competition of Tc-99m/stannous ions by the bindings sites; (iii) interference in the redox state of the labeling system, and (iv) blockage of calcium channels (Hesslewood et al, 1994;Bernardo-Filho et al, 2005). Results obtained from blood of animals treated with the extract, have shown that metabolization of Uncaria tomentosa extract after in vivo treatment was unable to alter the labeling of the blood constituents.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro effect of the Uncaria tomentosa extract on radiolabeling of blood constituents may be due to four possible mechanisms: (i) chelation of stannous and/or pertechnetate ions; (ii) competition of Tc-99m/stannous ions by the bindings sites; (iii) interference in the redox state of the labeling system, and (iv) blockage of calcium channels (Hesslewood et al, 1994;Bernardo-Filho et al, 2005). Results obtained from blood of animals treated with the extract, have shown that metabolization of Uncaria tomentosa extract after in vivo treatment was unable to alter the labeling of the blood constituents.…”
Section: Discussionmentioning
confidence: 99%
“…(Hesslewood and Leung, 1994;Owunwanne et al, 1995;Sampson, 1999). Blood constituents labeled with 99mTc have been used in several clinical examinations (Saha, 2004) and also as an experimental assay on an attempt to verify the effect of drugs ).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic drugs can modify the nature or amount of the 99mTc-radiopharmaceutical bound to blood constituents and result in an unexpected behavior of the radiopharmaceutical (Hladik III et al, 1987;Hesslewood and Leung, 1994;Sobal and Sinzinger, 2001;Welling et al, 2002;Fonseca et al, 2005). Thus, the evaluation of the influence of drugs on the fixation of 99mTc in blood constituents is important.…”
Section: Discussionmentioning
confidence: 99%